(untitled) (Research, Society and Development, 2022)
Objective: The sufferings arising from chronic renal failure affects (CRF) are multiple and harmful. Along with this finding, spiritual practices reduce the negative effects resulting from CRF, as well as stimulate the production of more optimistic expectations during the treatment of this disease. Thus, this work is structured around the following question: what are the benefits of spirituality for adult patients with chronic kidney disease undergoing hemodialysis? The general objective was to investigate the benefits of the spiritual approach for people with chronic kidney disease undergoing hemodialysis. Method: The method consisted of an integrative review by consulting the following databases: BVS, LILACS and Pubmed. As inclusion criteria, articles published in the last five years in Portuguese, English and Spanish were considered. The search strategy was as follows: chronic renal failure AND spirituality AND adult health. Results: 22 articles were selected, which contain information on the application of spirituality by chronic kidney patients undergoing hemodialysis in several countries. The acquisition of the obtained data signaled the adoption of practices such as hypnosis, meditation, yoga, prayers and Reiki. Conclusions: Spirituality has provided an improvement in the perception of the quality of life of individuals with chronic kidney disease undergoing hemodialysis. However, it is noted that there is a scarcity of research on the subject. The change in this condition will contribute so that the relevance of the spiritual focus in the daily life of health care networks can be definitively and deeply rooted.